OPPORTUNITIES OF FLOW CYTOMETRY IN DIAGNOSTICS OF INFECTIOUS DISEASES. PART 1 - S. V. Khaidukov (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. Development of a modern medical science demands more thorough and deeper approach to diagnostics of diseases. New diagnostic technologies for these investigations are necessary and flow cytometry is such technology. Modern achievements in the field of fluorescent dyes, development of laser and computer technologies, have led to wide use of the given technology in medical practice. Infectious immunology is not exception. Cytokines production analysis at tuberculosis, HLA-DR expression changes for monocytes and CD64 for granulocytes at sepsis are the important diagnostic attributes. Flow cytometry offers new approaches to early and faster diagnostics of infringements of immune system at tuberculosis and sepsis, allows supervising development of these pathologies more effectively and estimate efficiency of therapy.